Elastic realities - documentary practices between cinema and art - Cornelia Lund (ARS, 2019)
ABSTRACT Recently, documentary practices, including those working with moving images, have known an unprecedented boom in the art field, which provoked criticism but also led to fruitful discussions between the two fields of artistic documentary practices and the more traditional documentary cinema. This article aims to contribute to this discussion by analyzing some pivotal arguments of the ongoing debate, mainly the question of documentary practices and their relation to reality, art and politics. For a better understanding of the current situation, the analysis of key moments in the history of documentary discourse is the basis for the discussion of contemporary documentary practices between cinema and art, considering seminal examples combining moving images with questions of performativity.